ENDOPHORIC MARKERS IN ESP TEXTBOOKS - Bogdanović, Весна (Наслеђе, 2015)
Metadiscourse is an important element in writing scientific papers and as such it should be included in ESP courses and/or academic writing courses in higher education. The paper explores one type of metadiscourse markers – endophoric markers, in order to determine their usage in ESP textbooks. Endophoric markers present a segment of a writing skill that facilitates comprehension and supports arguments by referring to earlier propositional material or by anticipating the material that is to come. The aim of the paper is to present the number and examples of endophoric markers that can be found in three selected ESP textbooks and to compare them to the usage of these markers reported in studies on textbooks, as well as on several other forms of academic writing. The results will show that the usage of endophoric markers in ESP textbooks is not comparable to their usage in other forms of academic writing, and that the authors of future ESP textbooks should place more emphasis on this metadiscourse element.